Boron nitride nanotube-modified silicon oxycarbide ceramic composite: synthesis, characterization and applications in electrochemical energy storage - Abass, Monsuru A. (Kansas State University, 2017)
Polymer-derived ceramics (PDCs) such as silicon oxycarbide (SiOC) have shown promise as an electrode material for rechargeable Li-ion batteries (LIBs) owing to the synergy between its disordered carbon phase and hybrid bonds of silicon with oxygen and carbon. In addition to their unique structure, PDCs are known for their high surface area (~822.7 m² g⁻¹), which makes them potential candidates for supercapacitor applications. However, low electrical conductivity, voltage hysteresis, and first cycle lithium irreversibility have hindered their introduction into commercial devices. One approach to improving charge storage capacity is by interfacing the preceramic polymer with boron or aluminium prior pyrolysis. Recent research has shown that chemical interfacing with elemental boron, bulk boron powders and even exfoliated sheets of boron nitride leads to enhancements in thermal and electronic properties of the ceramic. This thesis reports the synthesis of a new type of PDC composite comprising of SiOC embedded with boron nitride nanotubes (BNNTs). This was achieved through the introduction of BNNT in SiOC pre-ceramic polymer at varying wt.% loading (0.25, 0.5 and 2.0 wt.%) followed by thermolysis at high temperature. Electron microscopy and a range of spectroscopy techniques were employed to confirm the polymer-to-ceramic transformation and presence of disordered carbon phase. Transmission electron microscopy confirmed the tubular morphology of BNNT in the composite. To test the material for electrochemical applications, the powders were then made into free-standing paper-like electrodes with reduced graphene oxide (rGO) acting as support material. The synthesized free-standing electrodes were characterized and tested as electrochemical energy storage materials for LIBs and symmetric supercapacitor applications. Among the SiOC-BNNT composite paper tested as anode materials for LIBs, the 0.25 wt.% BNNT composite paper demonstrated the highest first cycle lithiation capacity corresponding to 812 mAh g⁻¹ (at a current density of 100 mA g⁻¹) with a stable charge capacity of 238 mAh g⁻¹ when asymmetrically cycled after 25 cycles. On the contrary, the 0.5 wt.% BNNT composite paper demonstrated the highest specific capacitance corresponding to 78.93 F g⁻¹ at a current density of 1 A g⁻¹ and a cyclic retention of 86% after 185 cycles. This study shows that the free carbon content of SiOC-BNNT ceramic composite can be rationally modified by varying the wt.% of BNNT. As such, the paper composite can be used as an electrode material for electrochemical energy storage.
Keywords: Polymer-derived ceramics; Silicon oxycarbide; Lithium-ion battery; Supercapacitor